Changes in digestive cancer diagnosis during the SARS-CoV-2 pandemic in Italy: A nationwide survey. Issue 6 (June 2021) - Buscarini, Elisabetta; Benedetti, Antonio; Monica, Fabio; Pasquale, Luigi; Buttitta, Francesco; Cameletti, Michela; Ferrari, Clarissa; Ricciardiello, Luigi; ,; Massironi, Sara; Bianco, Maria Antonia; Germanà, Bastianello; et al.
Abstract: Background: The SARS-CoV-2 pandemic has had a huge impact on healthcare systems, resulting in many routine diagnostic procedures either being halted or postponed. Aims: To evaluate whether the diagnoses of colorectal, gastric and pancreatic cancers have been impacted by the SARS-CoV-2 pandemic in Italy. Methods: A survey designed to collect the number of histologically-proven diagnoses of the three cancers in gastroenterology services across Italy from January 1 to October 31 in 2017–2020. Non-parametric ANOVA for repeated measurements was applied to compare distributions by years and macro-areas. Results: Compared to 2019, in 2020 gastric cancer diagnoses decreased by 15.9%, CRC by 11.9% and pancreatic by 9.9%. CRC distributions showed significant differences between all years, stomach cancer between 2018 and 2020 and 2019–2020, and pancreatic cancer only between 2017 and 2019. The 2019–2020 comparison showed fewer CRC diagnoses in the North (-13.7%), Center (-16.5%) and South (-4.1%), fewer stomach cancers in the North (-19.0%) and South (-9.4%), and fewer pancreatic cancers in the North (-14.1%) and Center (-4.7%), with an increase in the South (+12.3%). Distributions of CRC and gastric cancer were significantly different between all years in the North. Conclusions: This survey highlights the concerning effects of the COVID-19 pandemic on the diagnostic yield of gastroenterology services for stomach, colorectal and pancreatic cancers in Italy.